Understanding and usage of the pronouns kami and kita among Indonesian millennial and generation Z - Ismail, Dario Rifki; Pranata, Aqil Julyanriko; Suriya, Azza Naila; Jaya, Patria Handung (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
The use of the pronouns kami and kita in Bahasa Indonesia is an issue for most Indonesian youths nowadays. Most of them use it incorrectly. This study explores the problematic usage of the pronouns kami and kita among Millennials and Gen Z in Indonesia. The research led to understanding how these generations comprehend and differentiate these words in daily use communication. A semantic approach is used to analyze the data since the basic difference between kami and kita pronouns is in the level of meaning. Interviews with ten respondents revealed that only three correctly understood the semantic differences between kami and kita. Most respondents understand the difference pragmatically, associating kami with formal contexts and kita with informal ones. Furthermore, most of them think that the difference between the two pronouns is in the number of subjects in a conversation. This misunderstanding often leads to incorrect usage in conversations. The study highlights the need for better awareness of semantic differences to avoid miscommunication. This research is expected to increase the awareness of Indonesian youths to use both pronouns correctly to avoid misunderstandings in communication.